Analisis Efisiensi dan Transparansi APBN Indonesia: Studi Kasus Tahun Terbaru - Putri Darma, Sernanda; Haliza, Nur; Aulia Br Ginting, Dela; Kemala, Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study tries to present an analysis of the efficiency and transparency of the 2023 APBN in Indonesia. This research then uses comparative descriptive qualitative analysis by collecting data, classifying, analyzing and comparing targets with budget realization in accordance with appropriate theory. The aim of this research is to determine the implementation of the State Revenue and Expenditure Budget efficiently and economically, efficiently and effectively. The data sources used in this research are financial reports, especially the budget and budget realization between the 2023 fiscal year period obtained from book II of the financial notes along with the state income and expenditure budget of the Ministry of Finance of the Republic of Indonesia.